2014
DOI: 10.1111/pedi.12249
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and youth diabetes: distinguishing characteristics between islet cell antibody positive vs. negative patients over time

Abstract: Objective Obese youth clinically diagnosed with type 2 diabetes (T2DM) frequently have evidence of islet cell autoimmunity. We investigated the clinical and biochemical differences, and therapeutic modalities amongst autoantibody positive (Ab+) vs. autoantibody negative (Ab-) youth at the time of diagnosis and over time in a multi-provider clinical setting. Study Design Chart review of 145 obese youth diagnosed with T2DM from January 2003 through July 2012. Of these, 70 patients were Ab+ and 75 Ab-. The two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…In addition, Ab + T2D patients were mostly non‐Hispanic whites, with less female representation and less frequent family history of DM. An evaluation of our clinic population of obese Ab + versus Ab – T2D patients at diagnosis and their clinical course over time revealed similar findings: Ab + youth were younger, had higher rates of ketosis, higher HbA1c and glucose concentrations, and lower insulin and C‐peptide concentration, compared with Ab – patients . The latter patients had higher BMI Z‐scores and cardiometabolic risk factors at diagnosis, and such differences persisted over time.…”
Section: Diagnosis Of T2d In Youthmentioning
confidence: 64%
See 4 more Smart Citations
“…In addition, Ab + T2D patients were mostly non‐Hispanic whites, with less female representation and less frequent family history of DM. An evaluation of our clinic population of obese Ab + versus Ab – T2D patients at diagnosis and their clinical course over time revealed similar findings: Ab + youth were younger, had higher rates of ketosis, higher HbA1c and glucose concentrations, and lower insulin and C‐peptide concentration, compared with Ab – patients . The latter patients had higher BMI Z‐scores and cardiometabolic risk factors at diagnosis, and such differences persisted over time.…”
Section: Diagnosis Of T2d In Youthmentioning
confidence: 64%
“…Of the 1206 youth screened and clinically considered to have T2D, 118 (9.8%) were antibody positive: 5.9% were positive for a single antibody and 3.9% were positive for both antibodies, making them ineligible for the TODAY study. In smaller scale studies, the reported rates of positive pancreatic autoantibodies in youth clinically diagnosed with T2D vary from 10% to 75% …”
Section: Epidemiology Of Youth T2dmentioning
confidence: 99%
See 3 more Smart Citations